The relationship between students’ understanding of IR 4.0 with the use of ICT in learning (Hubungan antara kefahaman pelajar tentang IR 4.0 dengan penggunaan ICT dalam pembelajaran) - Mohd Sani, Ismail; Noradilah, Abdul Wahab; Nor Asmawati, Ismail (2020)
The availability of communication and information technology (ICT) facilities have played an important role in making the learning and programming process (PdPc) successful in the 21st century. ICT has become a great medium for facilitating information sharing and discovery, especially in the education world. However, our country concerns about teachers' readiness to accept reforms in education. In addition, the level of ICT in teachers is still low and poor internet access is hindering the use of ICT among teachers, especially teachers who teach in rural schools. Therefore, this study aims to look at the relationship of ICT usage among students in the state of Terengganu with the advent of the industrial revolution 4.0. This study is a quantitative study by descriptive review and inference. The questionnaire was used as a research instrument to collect data and a total of 102 regular daily SMK students in Terengganu were selected as the study sample. The data of this study were analysed by descriptive and inferential analysis involving percentage, frequency, mean score, “Independent Samples T-Test” and correlation. The findings of this study indicate that there is no significant difference in the level of understanding of IR 4.0 based on gender and school location factors. The study also found that there was no significant difference in the use of ICT as a medium of learning based on school location. However, there is a significant correlation between the understandings of IR 4.0 on the use of ICT in learning. Therefore, it can be concluded that students in Terengganu state ICT as a means of gaining and sharing knowledge as well as the medium of learning today. The results of this study are expected to provide important information to the Ministry of Education Malaysia (KPM) in enhancing ICT integration in the PdPc process in schools.